Embodiment : essays on gender and identity - Thapan, Meenakshi; Nehru Memorial Museum and Library (Delhi ; New York : Oxford University Press, 1997)
Papers presented at an international workshop held in 1994.
"Nehru Memorial Museum & Library, New Delhi."
Includes bibliographical references and index.
Keywords: Gender identity -- India -- Congresses; Human body -- Social aspects -- India -- Congresses; Sex role -- India -- Congresses; India -- Religious life and customs -- Congresses